Predictive value of ASTRAL score modified by triglyceride glucose index for prognosis in ischemic stroke - PEI Lu-lu; CHAI Yuan; YANG Jun-zhe; YANG Jun-zhe; XU Yu-ming; SONG Bo (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To investigate the predictive value of a modified Acute Stroke Registry and Analysis of Lausanne (ASTRAL) score, in which the triglyceride glucose (TyG) index replaces the glucose parameter of ASTRAL score, for poor prognosis in ischemic stroke patients. Methods This study was based on the ischemic stroke database of The First Affiliated Hospital of Zhengzhou University. A total of 3393 ischemic stroke patients from January 2019 to December 2021 were enrolled. Baseline information was collected, and the TyG index and ASTRAL score were calculated. Replace the glucose parameter of ASTRAL score with the TyG index to construct ASTRAL‐TyG model. Modified Rankin Scale (mRS) score was used to evaluate the functional outcome. Univariate and multivariate Logistic regression analyses were performed to screen for influencing factors of poor prognosis. Receiver operating characteristic (ROC) curve was plotted, and the area under the curve (AUC), net reclassification improvement (NRI), and integrated discrimination improvement (IDI) were calculated to evaluate the predictive value of the ASTRAL-TyG model. Results Based on the mRS score, patients were stratified into a good prognosis group (mRS≤2, n=2961) and a poor prognosis group (mRS>2, n=432). Logistic regression analysis showed that both increased ASTRAL score witnin 24 h of admission (OR=1.156, 95%CI: 1.133-1.179; P=0.000) and increased TyG index (OR=1.731, 95%CI: 1.489-2.013; P=0.000) were risk factors for poor prognosis (Model 1, TyG index was included as a continuous variable). Increased ASTRAL score within 24 h of admission (OR=1.156, 95%CI:1.133-1.179; P=0.000), TyG index of 8.69-9.08 (OR=1.445, 95%CI:1.025-2.039; P=0.036), and TyG index≥9.55 (OR=2.103, 95%CI:1.532-2.888; P = 0.000) were risk factors for poor prognosis (Model 2, TyG index was included as a categorical variable). The ROC curve demonstrated that the AUC for predicting one year poor prognosis was 0.754 (95%CI:0.728-0.779, P=0.000) for the ASTRAL score and 0.768 (95%CI:0.743-0.794, P=0.000) for the ASTRAL‐TyG model. The sensitivity was 65.05% and 65.97%, while the specificity was 74.23% and 78.01%, respectively. The predictive value of the ASTRAL-TyG model was significantly higher than that of the ASTRAL score (Z=2.084, P=0.037). Conclusions The ASTRAL score modified by the TyG index (ASTRAL‐TyG model) improved the predictive value for poor prognosis in ischemic stroke patients.